Avaliação da resistência ao desgaste de revestimentos de aços inoxidáveis modificados com boro e fabricados por Plasma com Arco Transferido (PTA) - Sigolo, Erich (Universidade Federal de São Carlos, 2016)
The discovery of new promising oil extraction sites in Brazil coast led to a great search for novel functionalized materials to withstand the demanding conditions from offshore oil exploitation. Stainless steels, such as duplex, superduplex and supermartensitc grades, are well established materials for applications in which a good balance of cost, mechanical strength and corrosion resistance is required. However, depending on the environment and working conditions, for instance in the risers (which connect the well head on the sea floor to the platform), stainless steels might present unfavorable wear resistance. Consequently, there are coating processes that can deposit thicker layers of wear resistant materials (also called hardfacing) used for applications in which wear conditions are demanding. Also, recent studies conducted in DEMa/UFSCar showed that boron addition in stainless steels composition led to the formation of borides which increased wear resistance. In this work, the microstructure and wear resistance of boron-modified stainless steels coatings, namely superduplex and supermartensitic with different boron additions, produced by Plasma Transferred Arc (PTA) were investigated. This welding process allows the deposition of thick and dense coatings with metallurgical bonding and very low dilution. Microstructural characterization revealed that the coatings were dendritic in all cases, however the amount of borides formed was significantly different. The wear resistance was evaluated by dry sand/rubber wheel and reciprocating pin-on-plate tests. The results showed different wear resistance depending on wear mechanism involved. Although, in both tests, the wear resistance presented by the boron-modified superduplex coating was far superior. The formation of hard borides and its higher phase fraction in the microstructure were responsible for the good wear performance.
Wear resistance of boron-modified stainless steels coatings produced by Plasma Transferred Arc (PTA) Remove
Keywords: Aços inoxidáveis; Resistência mecânica; Desgaste; Corrosão; Plasma com Arco Transferido (PTA); ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA